2021
DOI: 10.5858/arpa.2021-0104-oa
|View full text |Cite
|
Sign up to set email alerts
|

Anterior or Posterior Prostate Cancer Tumor Nodule Location Predicts Likelihood of Certain Adverse Outcomes at Radical Prostatectomy

Abstract: Context.— Effect of tumor nodule (TN) location in the prostate on adverse radical prostatectomy (RP) outcomes is not well studied in contemporary cohort. Objective.— To investigate the significance of TN location with respect to extraprostatic extension (EPE), seminal vesicle invasion (SV+), and positive margin status (SM+) in 1388 RPs. Design.— Each TN at RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…This would account for the observed lower detection rates of APC, with the possibility that some cases progressed to an advanced stage and surgically incurable disease. Some recent studies have also demonstrated a high incidence of APC, ranging up to 30% of reported series 13,17,33. These studies are; however, not comparable with our current series of cases, as they included what were described as anterior dominant tumors, rather than cancers arising in and confined to the anterior prostate.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This would account for the observed lower detection rates of APC, with the possibility that some cases progressed to an advanced stage and surgically incurable disease. Some recent studies have also demonstrated a high incidence of APC, ranging up to 30% of reported series 13,17,33. These studies are; however, not comparable with our current series of cases, as they included what were described as anterior dominant tumors, rather than cancers arising in and confined to the anterior prostate.…”
Section: Discussioncontrasting
confidence: 66%
“…Some recent studies have also demonstrated a high incidence of APC, ranging up to 30% of reported series. 13,17,33 These studies are; however, not comparable with our current series of cases, as they included what were described as anterior dominant tumors, rather than cancers arising in and confined to the anterior prostate. Interestingly, in an earlier study, it was noted that the percentage of anterior tumors gradually increased from 10.8% in 2000 to 23.3% in 2004, which predated the widespread use of mpMRI.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, the zonal location offers no advantage over the well-established prognostic factors in predicting recurrence. Some more detailed anatomical differentiation (anterior, posterior, the apex of prostate, bladder neck) also revealed the difference in tumor location on prognosis [ 42 , 43 ]. Magheli et al found that tumors in the anterior prostate were associated with favorable pathological features and improved biochemical-free survival, although it was not an independent predictor of BCR [ 42 ].…”
Section: Discussionmentioning
confidence: 99%